Answer:
-8/3
Step-by-step explanation:
<u>Given</u>:
The system of linear equations are
and ![3x-2y=-5](https://tex.z-dn.net/?f=3x-2y%3D-5)
We need to determine the solution to the system of equations using substitution method.
<u>Solution</u>:
The solution can be determined using the substitution method.
Let us substitute
in the equation ![3x-2y=-5](https://tex.z-dn.net/?f=3x-2y%3D-5)
Thus, we have;
![3(4+y)-2y=-5](https://tex.z-dn.net/?f=3%284%2By%29-2y%3D-5)
![12+3y-2y=-5](https://tex.z-dn.net/?f=12%2B3y-2y%3D-5)
![12+y=-5](https://tex.z-dn.net/?f=12%2By%3D-5)
![y=-17](https://tex.z-dn.net/?f=y%3D-17)
Thus, the value of y is -17.
Substituting
in the equation
, we get;
![x+17=4](https://tex.z-dn.net/?f=x%2B17%3D4)
![x=-13](https://tex.z-dn.net/?f=x%3D-13)
Thus, the value of x is -13.
Hence, the solution to the system of equations is (-13,-17)
Answer:
2x(2x-1)
Step-by-step explanation:
![4 {x}^{2} - 2x \\ \\ = 2x(2x - 1) \\](https://tex.z-dn.net/?f=4%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%5C%5C%20%20%5C%5C%20%20%3D%202x%282x%20-%201%29%20%5C%5C%20)
Answer:
Step-by-step explanation:
Let M be the heights of men in the United States and W be the heights of women in the United States
Given that M is N(69.1, 2.9) and W (63.7, 2.7)
For a husband and wife we have average height as
=Z (say)
![Mean =E(z) = \frac{1}{2} [E(M)+E(W)] = 66.4 inches](https://tex.z-dn.net/?f=Mean%20%3DE%28z%29%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5BE%28M%29%2BE%28W%29%5D%20%3D%2066.4%20inches)
Var (Z) =![Var (\frac{x+y}{2} )=\frac{1}{4}[Var(x)+ Var(y)+2 cov (x,y)]\\](https://tex.z-dn.net/?f=Var%20%28%5Cfrac%7Bx%2By%7D%7B2%7D%20%29%3D%5Cfrac%7B1%7D%7B4%7D%5BVar%28x%29%2B%20Var%28y%29%2B2%20cov%20%28x%2Cy%29%5D%5C%5C)
=![0.25[2.9^2+2.7^2+2*r*sx*sy]\\= 0.25(20.398)\\=5.0995](https://tex.z-dn.net/?f=0.25%5B2.9%5E2%2B2.7%5E2%2B2%2Ar%2Asx%2Asy%5D%5C%5C%3D%200.25%2820.398%29%5C%5C%3D5.0995)
Mean = 66.4" and std dev = 2.258
Answer:
2 hours 15 minutes
Step-by-step explanation:
Given that :
Ben's speed = 3 mi/hr
One and half hours after Ben leaves = 1.5 hours
Ben's distance = 3 mi/hr * 1.5 = 4.5 miles
Amanda's speed = 5 mi/hr
Time taken before Amanda catches up:
Let time taken = x
Distance = speed * time
Ben's distance = Amanda's distance
4.5 mi + (3 * x) = 5 * x
4.5 + 3x = 5x
4.5 = 5x - 3x
4.5 = 2x
x = 4.5 / 2
x = 2.25 hours
Time taken = 2.25 * 60 = 135 minutes = 2 hours 15 minutes